Расчет неопределенности при проведении испытаний по определению группы горючести строительных материалов - Rogacheva, Т. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The main definitions of the «uncertainty» conception and the necessity of calculating uncertainty while testing in the field of fire safety are examined. Specific principles of calculation of uncertainty for defining the combustibility group in accordance with GOST 30244-94 «Building materials. The principles of testing for combustibility» (method 2) are represented.